Microglia shield the murine brain from damage mediated by the cytokines IL-6 and IFN-α - West, Phillip K.; Viengkhou, Barney; Campbell, Iain L.; Hofer, Markus J. (Frontiers in Immunology, 2022)
Sustained production of elevated levels of the cytokines interleukin (IL)-6 or interferon (IFN)-α in the central nervous system (CNS) is detrimental and directly contributes to the pathogenesis of neurological diseases such as neuromyelitis optica spectrum disorders or cerebral interferonopathies, respectively. Using transgenic mice with CNS-targeted production of IL-6 (GFAP-IL6) or IFN-α (GFAP-IFN), we have recently demonstrated that microglia are prominent target and effector cells and mount stimulus-specific responses to these cytokines. In order to further clarify the phenotype and function of these cells, we treated GFAP-IL6 and GFAP-IFN mice with the CSF1R inhibitor PLX5622 to deplete microglia. We examined their ability to recover from acute microglia depletion, as well as the impact of chronic microglia depletion on the progression of disease. Following acute depletion in the brains of GFAP-IL6 mice, microglia repopulation was enhanced, while in GFAP-IFN mice, microglia did not repopulate the brain. Furthermore, chronic CSF1R inhibition was detrimental to the brain of GFAP-IL6 and GFAP-IFN mice and gave rise to severe CNS calcification which strongly correlated with the absence of microglia. In addition, PLX5622-treated GFAP-IFN mice had markedly reduced survival. Our findings provide evidence for novel microglia functions to protect against IFN-α-mediated neurotoxicity and neuronal dysregulation, as well as restrain calcification as a result of both IL-6- and IFN-α-induced neuroinflammation. Taken together, we demonstrate that CSF1R inhibition may be an undesirable target for therapeutic treatment of neuroinflammatory diseases that are driven by elevated IL-6 and IFN-α production.